ARREST AND DETENTION OF ‘BOAT PEOPLE’ IN INDONESIA TERRITORY WATER - Davina Oktivana (Padjadjaran Journal of International Law, 2017)
AbstractAs a Coastal State, Indonesia has full sovereignty to implement its national regulations to prevent illegal fishing in their territorial waters. One example of prevention effort can be pointed out by the arrest and detention of hundreds of ‘boat people’ while they were conducting illegal fishing in Derawan Islands territory waters, East Kalimantan. They did transshipment and their fishing methods were prohibited regarding to Indonesian regulations. The issue of illegal fishing will be analyzed in regard to international law and as a part of the enforcement of Coastal State sovereignty. ‘Boat people’ refer to a group of people who spend most of their life and do all their activities in a boat, within the territorial waters of Indonesia, Malaysia and Philippines. The ‘boat people’ issues would be determined from two conceptions. The first one would be nationality issue. Most of the ‘boat people’ were proven to be stateless while few of them have been identified as citizen of Philippines. Indonesia and Malaysia authorities denied and did not recognize them as part of their nationality. It was contrary from what ‘boat people’ were claiming that they were originally from Semporna, Malaysia. Indonesia itself considered ‘boat people’ as a foreign fishers. There will be diverse approaches in dealing with those who hold a nationality and those who do not. The second conception would be concerning to the terminology of ‘traditional fishers’ and ‘traditional fishing rights’ based on international law and national regulation, and how state practices implement it. Furthermore, there would be comparison of international practices related to traditional fishing rights based on international law.Keywords: ‘boat people’, illegal fishing, nationality, stateless person, traditional fishing rights. AbstrakSebagai negara pantai, Indonesia mempunyai kedaulatan penuh untuk mengimplementasikan kebijakan nasionalnya untuk mencegah penangkapan ikan ilegal di wilayah perairan teritorialnya. Salah satu contoh dari tindakan pencegahan adalah penangkapan dan penahanan ratusan ‘manusia perahu’ pada saat mereka melakukan penangkapan ikan secara ilegal di perairan kepulauan Derawan, Kalimantan Timur. Mereka melakukan transit dan penangkapan ikan dengan metode yang dilarang oleh hukum Indonesia. Isu penangkapan ikan ilegal akan dianalisa dengan hukum internasional dan sebagai bagian dari penegakan kedaualatan negara pantai. ‘Manusia perahu’ mengacu pada sejumlah orang yang menghabiskan sebagian besar aktivitas hidupnya dalam kapal, dalam peraairan teritorial Indonesia, Malaysia dan Filiphina. ‘Manusia perahu’ berkenaan dengan dua konsep. Pertama adalah isu nasionalitas. Kebanyakan ‘manusia perahu’ terbukti tidak mempunyai kewarganegaraan, sedangkan sebagian dari mereka sudah diidentifikasi sebagai warga negara Filiphina. Otoritas Indonesia dan Malaysia tidak mengakui mereka sebagai bagian dari warga negara kedua negara ini. Hal ini sangat berlawanan dengan ‘manusia perahu’ yang melakukan klaim bahwa mereka berasal dari Semporna, Malaysia. Indonesia sendiri menganggap ‘manusia perahu’ sebagai penangkap ikan asing. Ada beberapa cara dalam menangani mereka yang telah mempunyai kewarganegaraan dan mana yang belum. Konsepsi kedua adalah berkenaan dengan terminilogi ‘penangkap ikan tradisional’ dan ‘hak menangkap ikan secara tradisional’ berdasarkan hukum internasional dan peraturan nasional, dan bagaimana praktik negara diimplementasikan. Lebih lanjut lagi, akan ada perbandingan mengenai praktik internasional berkenaan dengan hak memancing tradisional berdasarkan hukum internasional. Kata Kunci: ‘manusia perahu’, illegal fishing, kebangsaan, tak berkewarganegaraan, hak nelayan tradisional.